Volumetric Segmentation of Cell Cycle Markers in Confocal Images Using Machine Learning and Deep Learning - Khan, Faraz Ahmad; Voß, Ute; Pound, Michael P.; French, Andrew P. (Frontiers in Plant Science, 2020)
Understanding plant growth processes is important for many aspects of biology and food security. Automating the observations of plant development - a process referred to as plant phenotyping - is increasingly important in the plant sciences, and is often a bottleneck. Automated tools are required to analyse the data in microscopy images depicting plant growth, either locating or counting regions of cellular features in images. In this paper we present to the plant community an introduction to and exploration of two machine learning approaches to address the problem of marker localization in confocal microscopy. First, a comparative study is conducted on the classification accuracy of common conventional machine learning algorithms, as a means to highlight challenges with these methods. Second, a 3D (volumetric) deep learning approach is developed and presented, including consideration of appropriate loss functions and training data. A qualitative and quantitative analysis of all the results produced is performed. Evaluation of all approaches is performed on an unseen time-series sequence comprising several individual 3D volumes, capturing plant growth. The comparative analysis shows that the deep learning approach produces more accurate and robust results than traditional machine learning. To accompany the paper we are releasing the 4D point annotation tool used to generate the annotations, in the form of a plugin for the popular ImageJ (FIJI) software. Network models and example datasets will also be available online.